An evaluation of the Masupa-Tsela Youth Pioneers Program implemented by the Eastern Cape Department of Social Development and Special Programs within Mhlontlo Local Municipality - Xalisa, Qaqamba Yvonne (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.